Interior Rumah Berbagi Bagi Komunitas Pengrajin Aksesoris Manik di Surabaya - Ferensia Tioris; Laksmi Kusuma Wardani; Lucky Basuki (Intra, 2019)
The disruptive era Indonesian has been facing nowadays has brought many changes and development which has impacted the economics and industrial fields. Indonesia's Government has came with a solution through creative economy council, which has responsiblity for 16 sub sectors, with fashion as the growing sector. In Surabaya, there is one UKM which succesfully evolve as an accessories artisans since 2012. As an owner, Riski Hapsari has vision and mission for teaching women as many as possible, especially housewives, so that they have an accessories crafting skill which has sell value. The obstacle which was facing right now is how could a single space accomodate artisan's activities in order to raise productivity, people's interest and society's appreciation with Human Centered Design approaching method which intergrate collaborative, educative, creative, collective and home based creative economy aspects. For that, training space is designed as a solution to the obstacle. This training space offers Sharing House concept, which includes room for training, learning, selling and communicating for the artisans and housewives in order to create a creative and positive activity which collaborate and mutual sharing as a big family. The main reason of the designing is to give a chance to housewives to developing a profitable skill, which make Koleksikikie is better known and create digital economy ecosystem in Surabaya. The implementation of this Sharing House concept creates an activity space which includes arctistic making space, collaboration space, beads gallery, brainstorming space, creative garden, photo studio, book corner, office, sirculation area/parking lot, security pos, beads store and supporting space.